Pengaruh Pendapatan Asli Daerah, Ukuran Pemerintah Daerah, Dan Kompleksitas Pemerintah Daerah Terhadap Kelemahan Pengendalian Internal Pemerintah Daerah - M. Saferi; Erly Mulyani (Universitas Negeri Padang, 2020)
This study aims to examine the effect of local revenue, size of local government, and complexities of local government on internal control weaknesses in West Sumatra province. This study is categorized as causative research. The population in this study are local governments of West Sumatra province of 2014 to 2017. By using purposive sampling method, there were 19 local goverments as the research’s sample. The type of data used is secondary data and used is panel regression analysis. The results of this study indicate that local revenue, size of local government, and complexities of local government has no significant effect on internal control weaknesses of local governments.